Effect of Chalcogenophenes on Chiroptical Activity of Twisted Tetracenes: Computational Analysis, Synthesis and Crystal Structure Thereof - Gayathri Jothish Kumar; Benny Bogoslavsky; Sashi Debnath; Anjan Bedi (Molecules, 2023)
The synthesis of multiply substituted acenes is still a relevant research problem, considering their applications and future potential. Here we present an elegant synthetic protocol to afford tetra-peri-substituted naphthalene and tetracene from their tetrahalo derivatives by a Pd(0)-catalyzed C-C cross-coupling method in a single step. The newly synthesized tetracenes were characterized by NMR, HRMS, UV-vis spectrophotometry, and single-crystal X-ray diffraction (SCXRD). In addition, the first systematic computational study of the effect of chalcogenophenyl substitutions on the chiroptical properties of twistacenes was reported here. The gas phase computational studies using density functional theory (DFT) on a series of chalcogenophene-substituted tetracenes revealed that their chiroptical activity could be systematically increased via the atomistic tuning of peripheral substituents.